Treatment of Kidney Stones Using Extracorporeal Shock Wave Lithotripsy (ESWL) and Double-J Stent in Infants - Mehdi Younesi Rostami; Mehrdad Taghipour-Gorgikolai; Rayka Sharifian (Advances in Urology)
Background. Extracorporeal shock wave lithotripsy (ESWL) has progressively acquired popularity as being the gold standard treatment for upper urinary tract lithiasis in infants since 1980. Our aim was to evaluate the outcome of ESWL for kidney stones and the use of double-J stent in infants. Material and Methods. A prospective clinical trial study performed on 50 infants with renal calculi at pelvic admitted in the Urology ward of Shafa Hospital, Sari, Iran, between 2001 and 2010. Main outcome measure of our study was clearing stones after one or more consecutive sessions of ESWL. Results. The study included 50 patients with renal calculi at pelvic. Among them, there were 35 (70%) boys and 15 (30%) girls with the age ranging from 1 to 13 months (mean of 7 month ± 3 days). All of them were treated by standard ESWL using Simons Lithostor plus machine. The stone sizes ranged from 6 mm to 22 mm. Double-J stents were placed in 11 infants (22%) with stones larger than 13 mm. Most of the patients required only one ESWL session. Conclusion. Since there were no complications following ESWL treatment, we can conclude that, in short term, ESWL is an effective and safe treatment modality for renal lithiasis in infants. In addition, we recommend double-J stent in infants with stones larger than 13 mm.